Surgical Management Of The Supernumerary And Fused Teat In A Cow Heifer - Pal, Madan; Saharan, Sandeep; Dinesh; Potliya, Sandeep; Kumar , Sarvan (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Supernumerary teat (SNT) or hyperthelia is a congenital condition of the dairy cattles. These interfere in milking and predisposed for mastittis by entry of pathogens. The main teat, being bigger and conspicuous is quite distinguishable from the supernumerary teat. Physiologically, the supernumerary teat usually has no duct that connects to the primary mammary gland. In that case, it is vestigial and non-functional. In some other cases, it may be connected to small glands or even the main glands, in which case, it yields but small amount of milk compared to the primary or main teat when suckled (Thomas et al., 2008). In fused teats, skin of two teats is fused together at base without any involvement of the teat canal or muscle. Fused teats are infrequently seen in the buffaloes and rarely in the cows. SNT may be useful for teat grafting to restore teat anatomy during an acute damage to the primary teat tip (Saifzadehet al., 2005).